2011
DOI: 10.1093/pasj/63.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku Discovery of a Hard Component Varying Independently of the Power-Law Emission in MCG −6–30–15

Abstract: Focusing on hard X-ray variability, we reanalyzed Suzaku data of Type I Seyfert galaxy MCG-6-30-15 obtained in 2006. Intensity-sorted spectroscopy and a principal component analysis consistently revealed a very hard component that varies independently of the dominant power-law emission. Although the exact nature of this hard component is not yet identified, it can be modeled as a power-law with a photon index ∼ 2 affected by a partial covering absorption, or as a thermal Comptonization emission with a relative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Similarly, the middle vs. hard CCP, shown in figure 2(b), represents generally positive correlations, but the data scatter is too large for a linear fit. The scatter suggests the presence of a variable hard component independent of the dominant power-law, as reported in MCG-6-30-15 (Noda et al 2011). This issue will be studied elsewhere.…”
Section: Timing Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…Similarly, the middle vs. hard CCP, shown in figure 2(b), represents generally positive correlations, but the data scatter is too large for a linear fit. The scatter suggests the presence of a variable hard component independent of the dominant power-law, as reported in MCG-6-30-15 (Noda et al 2011). This issue will be studied elsewhere.…”
Section: Timing Analysismentioning
confidence: 55%
“…Because of its genuine broad-band sensitivity, Suzaku (Mitsuda et al 2007) obviously provides the best available mean to search AGN spectra for the expected MZC effects. Given these, we studied the archival Suzaku data of the Seyfert galaxy MCG-6-30-15, and successfully detected a hard X-ray component that varies independently of the dominant PL continuum (Noda et al 2011). This new component can be interpreted as a thermal Compton emission with a relatively high optical depth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we require that the intensity of the Kβ has to be 0. Cerruti et al (2011), andNoda et al (2011) suggest that the inner accretion disc in Mrk 509 might be highly ionised, and thus the ionised emission of the Fe K complex might be associated to a relativistic ionised reflection component produced in the inner disc. To test this hypothesis, we substitute the two narrow lines (Fe xxv and Fe xxvi) with one broad ionised line (model 4 in Table 1) with a relativistic profile (disc line profile for a Schwarzschild black hole; diskline model in Xspec).…”
Section: The Mean Spectrummentioning
confidence: 99%
“…On the other hand, a steep primary continuum, which can be explained by a PL model with Γ  2.3, is dominant in X-rays from highly accreting AGNs such as narrow-line type 1 Seyferts (e.g., Laor et al 1994;Boller et al 1996). Recently, Noda et al (2011aNoda et al ( , 2013aNoda et al ( , 2014 revealed that these primary continua,both flat and steep, are simultaneously present in the X-ray emission from multiple Seyfert galaxies. The presence of these different primary X-rays may represent the presence of several distinct types of coronae with different electron temperatures and optical depths.…”
Section: Introductionmentioning
confidence: 99%